Improving treatment for Parkinson's disease: Harnessing photothermal and phagocytosis-driven delivery of levodopa nanocarriers across the blood-brain barrier - Kaili Liang; Li Yang; Jiawei Kang; Bo Liu; Ding Zhang; Liyan Wang; Wei Wang; Qing Wang (Asian Journal of Pharmaceutical Sciences)
Parkinson's disease (PD) poses a significant therapeutic challenge, mainly due to the limited ability of drugs to cross the blood-brain barrier (BBB) without undergoing metabolic transformations. Levodopa, a key component of dopamine replacement therapy, effectively enhances dopaminergic activity. However, it encounters obstacles from peripheral decarboxylase, hindering its passage through the BBB. Furthermore, levodopa metabolism generates reactive oxygen species (ROS), exacerbating neuronal damage. Systemic pulsatile dosing further disrupts natural physiological buffering mechanisms. In this investigation, we devised a ROS-responsive levodopa prodrug system capable of releasing the drug and reducing ROS levels in the central nervous system. The prodrug was incorporated within second near-infrared region (NIR-II) gold nanorods (AuNRs) and utilized angiopep-2 (ANG) for targeted delivery across the BBB. The processes of tight junction opening and endocytosis facilitated improved levodopa transport. ROS scavenging helped alleviate neuronal oxidative stress, leading to enhanced behavioral outcomes and reduced oxidative stress levels in a mouse model of PD. Following treatment, the PD mouse model exhibited enhanced flexibility, balance, and spontaneous exploratory activity. This approach successfully alleviated the motor impairments associated with the disease model. Consequently, our strategy, utilizing NIR-II AuNRs and ANG-mediated BBB penetration, coupled with the responsive release of levodopa, offers a promising approach for dopamine supplementation and microenvironmental regulation. This system holds substantial potential as an efficient platform for delivering neuroprotective drugs and advancing PD therapy.